Research on Grounding Fault Identification Method of DC 600 V Power Supply System Based on Random Forest - Zhou ZENG; Zixian LI; Wei DONG; Jian GUO; Jie CAI (机车电传动)
In order to solve the problem that the current DC 600 V power supply system can only diagnose a few of fault modes and has poor universality, a simulation model of DC 600 V power supply system was built, and various fault modes of power supply system were analyzed, such as input terminal, intermediate circuit, output terminal grounding, etc.; The key features of fault waveform were selected and extracted, then the random forest classifier method was used to solve the problem that the existing diagnosis methods were not universal. The verification results show that the method can accurately diagnose multiple ground fault modes, and has better universality and maintainability.